2010
DOI: 10.1243/03093247jsa608
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the forming limit diagram of AA 5182-O

Abstract: The prediction of a forming limit diagram (FLD) for aluminium alloy sheet using finite element analysis without implementing pre-defined geometrical imperfections or material imperfections is studied. The limit strains of the FLD are determined by applying a new proposed localization criterion in the dome stretching test. The elements just outside the necking area, where their major and minor principal strains have no simultaneous change after localized necking happens, are chosen as the reference elements for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Tensile deformation behavior of aluminum alloys in the warm working temperature range at different strain rates has been studied by several researchers. [8][9][10][11][12][13] Shehata et al 14 performed tensile tests of several Al-Mg alloys in the temperature range of 20°C-300°C. They observed that total elongation increased by five times when temperature was increased from 20°C to 300°C.…”
Section: Introductionmentioning
confidence: 99%
“…Tensile deformation behavior of aluminum alloys in the warm working temperature range at different strain rates has been studied by several researchers. [8][9][10][11][12][13] Shehata et al 14 performed tensile tests of several Al-Mg alloys in the temperature range of 20°C-300°C. They observed that total elongation increased by five times when temperature was increased from 20°C to 300°C.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the expenses involved by the experimental procedures of FLC construction, the theoretical (Hill, 1952;Marciniak and Kuczynski, 1967) and numerical (Li et al, 2010) methods have been more attractive to researchers. One of the suitable theoretical approaches for determination of the FLC is the Gurson-Tvergaard-Needleman (GTN) damage model (Gurson, 1977;Tvergaard, 1981Tvergaard, , 1982Tvergaard and Needleman, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Nakazima hemispherical punch experiment, the FE model including sheet, punch, die and blank holder is shown in the Figure 2. 30 The various dimensional parameters of the model are set according to the standard GB/T 15825.8-2008 “Sheet metal formability and testing methods-Guidelines for the determination of forming-limit diagrams.” The detailed dimensions are shown in Table 1.…”
Section: Finite Element Simulation Based On Abaqusmentioning
confidence: 99%